Cele Unii Europejskiej w świetle Agendy lizbońskiej z 2000 r. - Noga, Marian (European Union Objectives in Terms of Lisbon Agenda 2000, 2005)
The author presents modified European Union objectives, that were originally enclosed in the European Economic Community Treaty. The Lisbon strategy, which is being analysed in the article, consists of 4 elements: 1) innovations in the economy as an effect of economy based on knowledge; 2) liberalization of the telecommunication, energy transportation and financial markets; 3) development of enterpreneurship as a result of facilitation in founding and running a business; 4) social coherence creating a new, active model of a welfare state. At the end of the article a special attention is paid to estimating law system convergence between Poland and the European Union.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1056, s. 9-14